Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1188/16.cjon.555-556
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Fosaprepitant in Patients Receiving Emetogenic Regimens

Abstract: Fosaprepitant dimeglumine (Emend IV®) is an IV antiemetic that may be beneficial to patients receiving highly emetogenic regimens. Aprepitant (Emend®) is an oral medication that is administered for three consecutive days, whereas fosaprepitant is a single-dose IV medication that is administered on the day of chemotherapy for 20–30 minutes (depending on the IV access type). Fosaprepitant may be useful, yet it can also present a risk for hypersensitivity reactions and phlebitis. Oncology nurses must be aware of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
10
1
Order By: Relevance
“…3). In contrast, such inflammation at the vascular tissue was not observed in the FAP-D and AP groups in the present study, even though it was reported that FAP alone and EPI alone can cause infusion site adverse events (49). In clinical practice, complaints of vascular pain from patients also appeared after switching from oral AP to intravenous FAP.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…3). In contrast, such inflammation at the vascular tissue was not observed in the FAP-D and AP groups in the present study, even though it was reported that FAP alone and EPI alone can cause infusion site adverse events (49). In clinical practice, complaints of vascular pain from patients also appeared after switching from oral AP to intravenous FAP.…”
Section: Discussioncontrasting
confidence: 86%
“…AP is taken orally and FAP is administered intravenously to prevent systemic adverse events such as nausea and vomiting. Oral AP is ingested once before and twice after EPI treatment, once/day for 3 days mostly for inpatients, and intravenous FAP is administered once by constant-rate infusion over 30 min just before EPI treatment mostly for outpatients (4). It has been reported that intravenous FAP alone and an intravenous anthracycline such as doxorubicin alone can cause infusion-site adverse events (49).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fosaprepitant is a neurokinin 1 receptor (NK-1R) antagonist that binds and deactivate NK-1R leading to downstream effect such as Ca 2+ signaling through the g-protein coupled receptor (GPCR) cascade, which in turn leads to cellular sequestration resulting in vomiting [24][25][26] . Fosaprepitant exerts its effect on targeted cells by passing across the blood brain barrier (BBB) to its target destination 23 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Docetaxel has also demonstrated efficacy and tolerability in the neoadjuvant treatment of operable breast cancer. 6,7 The conventional formulation of docetaxel has several toxicity issues related to its excipients, polysorbate 80 and ethanol, such as acute hypersensitivity reactions, 8,9 cumulative fluid retention, 10 peripheral neuropathy, 11 severe anaphylactoid reactions, 12 infusion-site reactions, 13 and alcohol intoxication. 14,15 Corticosteroids and antihistamines are used as premedication to overcome these toxicities, [16][17][18] but these adverse effects may still occur in some patients.…”
Section: Introductionmentioning
confidence: 99%